Joint Optimization of Spectrum and Power Control in 6G Multi-UAV Networks: Managing Data Redundancy - Mohammad Ahmed Alnakhli (IEEE Access, 2025)
This paper investigates the joint spectrum and energy efficiency in multimanned aerial vehicle (Multi-UAV) communication network in environments beyond the fifth generation and sixth generation (B5G / 6G), with a focus on the challenges posed by redundant data. We propose a linear optimization model for bandwidth allocation that accounts for both correlated and uncorrelated data scenarios. Additionally, we enhance energy efficiency through the Augmented Lagrangian method for power control optimization. Our approach achieves superior joint spectrum and energy efficiency, with spectrum efficiency reaching 0.75 bits/Hz, outperforming other methods by effectively exploiting data correlation. Furthermore, the proposed approach demonstrates a significant improvement in energy efficiency under varying levels of source correlation, achieving up to 7 Mb/J as the correlation variance increases. These results highlight the crucial role of data correlation in optimizing joint spectrum and energy efficiency, making the proposed approach highly effective for future 6G multi-UAV networks in smart city environments, with an emphasis on reliability.